American Political History : A Very Short Introduction - Donald T. Critchlow (Oxford University Press, 2015)
The Founding Fathers who drafted the United States Constitution in 1787 distrusted political parties, popular democracy, centralized government, and a strong executive office. Yet the country's national politics have historically included all those features. In American Political History: A Very Short Introduction, Donald Critchlow takes on this contradiction between original theory and actual practice. This brief, accessible book explores the nature of the two-party system, key turning points in American political history, representative presidential and congressional elections, struggles to expand the electorate, and critical social protest and third-party movements. The volume emphasizes the continuity of a liberal tradition challenged by partisan divide, war, and periodic economic turmoil.